Entre revendications nationales et expériences locales. La reconnaissance des Premières Nations dans les universités de Montréal (Québec) - Léa Lefevre-Radelli; Emanuelle Dufour (Les éditions de la Maison des sciences de l'Homme, 2016)
This article is based on an anthropological and qualitative study conducted between 2013 and 2015 in the four universities of Montréal with Aboriginal Student Services' staff and First Nations students. The objective of the research was to understand the modalities of inclusion of indigenous realities in a non-Aboriginal academic environment. The study highlights two main elements. First, there is a distinction between the policies of English-speaking and French-speaking universities regarding the inclusion of Aboriginal perspectives. This reflects a specific political, geographical and linguistic situation in Quebec. Furthermore, the expectations expressed by the participants primarily concern the establishment of facilities to create a favorable environment and a greater cultural sensitivity outside the courses themselves. The radical transformation of curricula and teaching methods, at the heart of the reflection of indigenous intellectuals, which is promoted internationally by the UN, thus appears to be a real but secondary issue. This observation leads to a nuanced discussion on the concept of "indigenization of the curriculum".